English Bazar in Colonial Bengal : An Urban History of Malda (1813-1947) - Sarkar, Rupan (Brill | Manohar Publishers & Distributors, 2021)
India has a long history of urbanization from the time of the Indus Valley civilization to the modern age, and it bears specific characteristics relating to their historical circumstances. The urban centre that developed in Malda district of West Bengal during the period specified is categorically different from urbanization in the pre-colonial period. The urbanization at Lakhnauti in Bengal is archaeologically not very notable. The second urbanization that started there in the thirteenth century was the beginning of the process of urbanization in Malda and was identical to the features of any Muslim capital centric urban centre. The first British urban establishment that took place in the district during the pre-colonial phase originated with the establishment of the commercial factory of the East-India Company at English Bazar in 1680. However, a new type of urbanization took place after the formation of the Malda district in 1813. The nucleus of the administrative headquarters was located in the pre-colonial English settlement area popularly known as English Bazar. The gradual expansion of the city necessitated by administration and the need to accommodate the influx of migrants over the years from different areas of Bengal, led the district to assume a definite shape after establishment of the English Bazar Municipality in 1869. This book is an important contribution to the literature on the urbanization of colonial India at the micro level. It discusses conceptual as well as theoretical issues relating to urbanization, urban experiences of pre-colonial and colonial India, and the origin and growth of the English Bazar town.